Exploring the impact of preservice teacher internship programs on students’ perception of the teaching profession - Muhammad Bukhori Dalimunthe; Reza Aditia; Ainul Mardhiyah; Riza Indriani; Rosmala Dewi (Institute of Advanced Engineering and Science, 2024)
This study aims to analyze how the preservice teacher internship program influences students’ perception of the teaching profession by examining the variables of reaction, learning experiences, behavior, and the mediating role of results. By examining these variables, the study synthesizes findings from multiple studies and incorporates them. Using a survey conducted among students at a university in Medan, Indonesia, the study collected data electronically through the distribution of a questionnaire via Google Forms. The sample consisted of 252 students, and partial least square structural equation modeling (PLS-SEM) was employed to analyze the data. The outer models (measurement) and inner model (structural relations among latent variables) were validated and evaluated. The results indicate significant positive direct effects of reaction, learning, and behavior on results. Moreover, the results from the preservice teacher internship program have a significant positive effect on students’ perceptions. The study also reveals that results act as a partial mediator in the relationships between behavior and perception, learning and perception, and reaction and perception.